Greening Water Risks Natural Assurance Schemes - López-Gunn, Elena; van der Keur, Peter; Van Cauwenbergh, Nora; Le Coent, Philippe; Giordano, Raffaele (Water Security in a New World, 2023)
Confronted with an increase in floods, droughts and other natural hazards, cities and regions are alert to find climate proof solutions that overcome the limitations of traditional grey infrastructure. Nature-based solutions are proposed as a valid way to address risk and adapt to climate change while increasing resilience through the multiple benefits they generate. However, in spite of the widespread academic and political support for NBS, their implementation is lacking. As key barriers to implementation there are institutional and regulatory barriers, an absence of clear evaluation of NBS performance, funding/financing barriers and knowledge and acceptance barriers. This Open Access book provides a hands-on guide to overcome these barriers, through the stepwise creation of nature-assurance schemes that operationalize the insurance value of ecosystems. At the basis thereof is an integrated biophysical, economic and social assessment which is integrated with implementation considerations through the generation of business models and blended funding and financing schemes. This book will be of interest to practitioners and researchers who want to better understand how to operationalize the insurance value of ecosystems. The book provides 9 DEMO examples on the application of this method across different scales: urban, medium and large catchments and target both floods and droughts.